La emboscada - Daranas, Ernesto, 1961-; Molina Alonso, Ania; Wood, Patricio; Cao, Tomás; Casas, Caleb; Gómez, Armando Miguel (Instituto Cubano del Arte e Industria Cinematográficos, 2014)
Four men escape from an ambush where the enemy never shows his face. Their personal stories will begin to unfold from a distressing situation limit, where the scarcity of resources, physical exhaustion and contradictions will cause unexpected behavior that will jeopardize any chance of survival.